Upaya Meningkatkan Hasil Belajar Lempar Turbo Melalui Permainan Bola Berekor Pada Siswa Sekolah Dasar - Ahlunnazar, Ahlunnazar; Subagio, Subagio; Taufik, Kurnia (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This study aims to determine the increase in learning outcomes of turbo throwing through a tail ball game. This research method uses Classroom Action Research (PTK). This research was conducted in two cycles, with each cycle consisting of planning, implementing action, observing, and reflecting. The research subjects were grade IV students of SDN 2 Gunung Rajak for the 2019/2020 academic year, totaling 12 boys, 6 people and 6 girls. Data collection techniques through turbo throwing ability tests and observation of the learning process. The validity of the data uses triangulation techniques. Data analysis using descriptive techniques using percentage techniques to see trends that occur in learning activities. The initial condition before the PTK was carried out, there were only 3 students who had finished learning to throw the turbo. In the first cycle increased to 8 students. Cycle II increased to 10 students. The game of tail ball made a significant contribution to the increase in turbo throwing results. The conclusions of this study are as follows: The game of tail ball can improve the learning outcomes of turbo throwing in grade IV SDN 2 Gunung Rajak students for the 2019/2020 academic year. The achievement of the learning outcomes of turbo throwing from the initial conditions to the first cycle is 42%. From cycle I to cycle II amounted to 16%. The increase in completeness of learning outcomes as a whole from the initial conditions to cycle II was 58%.